Perencanaan Persediaan Bahan Baku Fresh Fruit Pada PT. XYX Unit Denpasar - Simbolon, Agnes; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
PT. XYZ is one company that has produced food for airlines. The production process will run if there is an inventory of raw materials to be used. The purpose of this research is to find out which types of fresh fruit raw materials have the highest demand, to know the planning and calculation of raw material supplies, to know the safety stock and reorder points for raw materials at PT. XYZ Unit Denpasar. Data collection methods in this research are literature studies, interviews, observations, field practice and data from companies in collecting primary and secondary data. The analytical tools used are SAP and Microsoft Excel applications using the Economic Order Quantity (EOQ) and Re Order Point (ROP) methods. By using this method, the raw material for fresh fruit is watermelon with optimal quantity results of 375 Kg for seven orders, pineapple fruit 443 Kg for nine orders, while papaya fruit 392 Kg for eight orders. Through the calculation of Safety Stock and Re Order Point, for fresh fruit raw materials that have the highest safety stock based on historical demand, namely papaya fruit has a Safety Stock of 139 and a Re Order Point of 161, pineapple has a Safety Stock of 129 and a Re Order Point of 155, and Watermelon has a Safety Stock of 74 and a Re Order Point of 94.